OBSTRUCTIVE SLEEP APNEA SYNDROME IN CONGESTIVE HEART FAILURE: CARDIOLOGIST PERSPECTIVE - E. A. Medvedeva; L. S. Korostovtseva; Yu. V. Sazonova; M. V. Bochkarev; Yu. V. Sviryaev; A. О. Konradi (Российский кардиологический журнал)
In the review, the data presented, on sleep disordered respiration in chronic heart failure patients with emphazis on sleep apnea syndrome (SAS). The aspects of prevalence are discussed, as of pathogenesis, diagnostics and specifics of SAS management in decreased or normal ejection fraction. The original results presented, on the disordered breathing assessment in patients with severe systolic dysfunction. The necessity underscored for personalized diagnostic and management approach to obstructive sleep apnea syndrome which is not just a risk factor for heart failure, but is a comorbidity at various stages of cardiovascular continuum.